2018
DOI: 10.1073/pnas.1807439115
|View full text |Cite
|
Sign up to set email alerts
|

N-glycan microheterogeneity regulates interactions of plasma proteins

Abstract: SignificanceGlycosylation is one of the most common and complex posttranslation modifications that significantly influences protein structure and function. However, linking individual glycan structures to protein interactions remains challenging and typically requires multiple techniques. Here, we establish a mass-spectrometric approach to systematically dissect the microheterogeneity of two important serum proteins, α1-acid glycoprotein and haptoglobin, and relate glycan features to drug and protein-binding i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
132
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(138 citation statements)
references
References 56 publications
(75 reference statements)
6
132
0
Order By: Relevance
“…Eight N-glycopeptides form alpha-2-HS-glycoprotein, ceruloplasmin, haptoglobin, kininogeN-1, and vitronectin, were confirmed with the study of liver-secreted N-glycoproteins, where bi-and tri-antennary glycopeptides were most common ones from HCC plasma 22,25 . Fucosylation of AGP and haptoglobin inhibits the biding with drug and hemoglobin, respectively 48 . We also classified 20 fucosylated N-glycopeptides from complement components C7, IgA2, IgJ, IgM, alpha-1-antichymotrypsin, alpha-2-HS-glycoprotein, AGP, apolipoprotein D, ceruloplasmin, hemopexin, and phospholipid transfer protein as core fucosylated.…”
Section: Resultsmentioning
confidence: 99%
“…Eight N-glycopeptides form alpha-2-HS-glycoprotein, ceruloplasmin, haptoglobin, kininogeN-1, and vitronectin, were confirmed with the study of liver-secreted N-glycoproteins, where bi-and tri-antennary glycopeptides were most common ones from HCC plasma 22,25 . Fucosylation of AGP and haptoglobin inhibits the biding with drug and hemoglobin, respectively 48 . We also classified 20 fucosylated N-glycopeptides from complement components C7, IgA2, IgJ, IgM, alpha-1-antichymotrypsin, alpha-2-HS-glycoprotein, AGP, apolipoprotein D, ceruloplasmin, hemopexin, and phospholipid transfer protein as core fucosylated.…”
Section: Resultsmentioning
confidence: 99%
“…The glycoform AFP‐L3, but not L1 or L2, is the marker for hepatocellular carcinoma. Wu and coworkers have reported that N‐glycan heterogeneity of α1‐acid glycoprotein (AGP) and haptoglobin (Hp) will regulate the interactions of plasma proteins. Meanwhile, it has been reported that phosphorylation of Hsp90 can affect its interaction with co‐chaperones or client proteins .…”
Section: Discussionmentioning
confidence: 99%
“…Differences in glycan composition contribute greatly to glycosite heterogeneity, but structural isomers also contribute, such as conformational isomers (α vs β) or linkage differences (e.g., α2,3-linked vs. α2,6-linked sialic acid). Microheterogeneity can vary glycosite by glycosite or can be somewhat uniform across a given glycoprotein, and differences in glycan structures at a single glycosite can alter biological relevance (31)(32)(33)(34)(35)(36). The term "metaheterogeneity" has recently been proposed to describe these levels of variation across glycosites of a given protein (37).…”
Section: Introductionmentioning
confidence: 99%